Az egészségügy területi egyenlőtlenségei – az újraértelmezés szükségességéről - Orosz, Éva (Tér és Társadalom, 1989)
The starting point of the paper at the study ot regional inequalities is the fact that public health is embedded in the socio-economic environment. Therefore the present inequalities of the system of Hungarian public health are discussed as an element of the interwined crisis of the health, economic and political shperes. The paper, dealing with the state of health, shows that the trend of the life expectancy of the Hungarian population has turned away from the one in the advanced Western countries, further on, it indicates that the trend is accompanied by the increasing social and regional differences of mortality. This phenomenon can be interpreted as the ’social cost’ of the post-1945 socio-economic development. The paper lays emphasis on the study of the systemic inequalities among the inequalities of the health care, in other words, it wishes to explore the immanent inequalities of the structure and mechanisms of the health system and the effects of the health system upon the inequalities originating outside health care. It wanted to show that the overcentralized health care administration, its system built downwards from the top, the rigid, overcentralized regional functional structure of services constitute part of the inequalities of health care interpreted in a broad sense. In fact these phenomena manifest the unequal power position of certain groups, or shperes of society, or of certain actors of health care in relation to command over resources. We regard the system of political institution evolved by state socialism in the early 50s to be the basic reason of the systemic inequalities ot health care.